Irrigation vs. closed drainage in the treatment of chronic subdural hematoma - Erol, FS; Topsakal, C; Ozveren, MF; Kaplan, M; Tiftikci, MT (Churchill Livingstone, 2005)
A number of different techniques are used to treat chronic subdural hematomas surgically. In this study, 70 chronic subdural hematomas were surgically treated and analyzed prospectively. Patients were classified according to clinical features and computed tomography images. Results of the cases that underwent burr-hole craniostomy-irrigation (group A; n = 35) were compared with those undergoing burr-hole craniostomy-closed system drainage (group B; n = 35). The most common etiological factor was trauma in both groups. Complete resolution in the early period was higher in group B compared to group A (60% vs. 40%). However, no difference was noted at the first month-follow-up. Recurrence rates were 17% in group A and 14% in group B. No significant difference was noted in terms of hospitalization duration or postoperative complications. In conclusion, we believe that the burr-hole craniostomy-irrigation technique is a reliable and effective method compared to burr-hole craniostomy-closed system drainage in the treatment of chronic subdural hematoma. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: chronic subdural hematoma; burr-hole craniostomy; closed system drainage